2016
DOI: 10.3945/ajcn.116.136911
|View full text |Cite
|
Sign up to set email alerts
|

Public health economic evaluation of different European Union–level policy options aimed at reducing population dietary trans fat intake

Abstract: Background: The adverse relation between dietary trans fatty acid (TFA) intake and coronary artery disease risk is well established. Many countries in the European Union (EU) and worldwide have implemented different policies to reduce the TFA intake of their populations.Objective: The aim of this study was to assess the added value of EU-level action by estimating the cost-effectiveness of 3 possible EU-level policy measures to reduce population dietary TFA intake. This was calculated against a reference situa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…We found no empirical studies investigating the sole effect of labels showing the TFA content of food products, but we included five modelling studies (two of good quality, 32 , 33 two fair 34 , 35 and one of poor quality 36 ). In the Netherlands a healthier choices logo for food packages was implemented in 2006.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found no empirical studies investigating the sole effect of labels showing the TFA content of food products, but we included five modelling studies (two of good quality, 32 , 33 two fair 34 , 35 and one of poor quality 36 ). In the Netherlands a healthier choices logo for food packages was implemented in 2006.…”
Section: Resultsmentioning
confidence: 99%
“…However, compared with taking no action, this option incurred greater costs than it saved, in terms of health-care costs, lost productivity and implementation costs. 33 In a similar approach to the Dutch study, researchers in Brazil investigated replacing products with ones that complied with a healthy choices logo. 36 Estimated TFA intakes were 0.8 g/day (standard deviation, SD: 1.0) for typical menus, 0.1 g/day (SD: 0.2) for the choices menus and 0.2 g/day (SD: 0.3) for energy-adjusted choices menus, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…In 2010, estimated intakes varied from 0.2 to 6.5 En% worldwide [ 10 ]. At present, many countries actively work on measures to further lower industrial trans fat levels in foods [ 7 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…This was very clearly demonstrated by Martin-Saborido et al [35] in an economic simulation of the effects of different anti-iTFA strategies using the example of the EU. They predicted that an EU-level legal limit on iTFA would be the optimal action, considering both the number of averted CVD-related disease-adjusted life years (DALYs) and associated cost savings in public healthcare.…”
Section: Prospects For Solving the Problem Of Industrial Tfamentioning
confidence: 74%
“…Fortunately, this problem is fairly easy to solve via proper legislation. The experience of multiple countries has shown that banning iTFA use is an effective and feasible approach, leading to lower CVD morbidity and mortality [7,22,26,35]. Thus, it appears reasonable that cardiology societies around the world, both national and international, should strive to raise public awareness about the issue and lobby for implementing anti-iTFA laws either on the level of individual countries or, if possible, on the level of international entities like the EU.…”
Section: Resultsmentioning
confidence: 99%